Efektivitas reduksi mikroba pada tempura PT. XYZ melalui perlakuan suhu penyimpanan dan konsentrasi kitosan sebagai edible coating - Yunita Siti Mardhiyyah; Ghaniy Samudra; Irvan Adhin Cholilie (AGROINTEK, 2026)
Food goods may become contaminated by microorganisms or improperly stored, among other reasons. The product that PT. XYZ processes are tempura, which is easily destroyed. High microbiological activity during the product's shelf life is the cause of the damage factor. Handling during improper storage has an impact on the product's overall microbe count rise. As an alternative to treating product degradation from bacteria, chitosan can be utilized as an edible covering. In addition to serving as a product coating to shield the item from physical harm, the edible coating also contains chitosan. This antibacterial inhibits the growth of microorganisms in the product. The efficiency of the reduction of microbial growth is influenced by the varied chitosan concentrations. The chitosan concentrations utilized in this investigation varied from 0% (control sample) to 0.6%, 0.8%, 1.0%, 1.2%, and 1.4% (concentration changes). Observations were made regarding the harm to the organoleptic qualities of tempura goods, the actual difference, the best overall reduction, and the efficacy of microbial reduction. Statistical tests were used for significance differences. According to research findings, a 1.2% coating concentration combined with a lowering temperature treatment demonstrated the highest degree of efficacy in terms of microbial suppression, reaching 1.32x10-5 CFU / with a 2-week shelf life based on tempura organoleptic qualities. The 1.2% sample that underwent storage treatment at room temperature had the best concentration and the most effective microbial decrease, with a two-day shelf life of 3.03x105 CFU/mL.